2018
DOI: 10.1111/mec.14470
|View full text |Cite
|
Sign up to set email alerts
|

Landscape attributes governing local transmission of an endemic zoonosis: Rabies virus in domestic dogs

Abstract: Landscape heterogeneity plays an important role in disease spread and persistence, but quantifying landscape influences and their scale dependence is challenging. Studies have focused on how environmental features or global transport networks influence pathogen invasion and spread, but their influence on local transmission dynamics that underpin the persistence of endemic diseases remains unexplored. Bayesian phylogeographic frameworks that incorporate spatial heterogeneities are promising tools for analysing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 85 publications
2
68
0
Order By: Relevance
“…Further, the analysis of metadata associated with these Iranian clades suggests frequent RABV transmissions between dog and wildlife animal populations, and vice versa. Such a complex transmission pattern has already been identified in other regions such as Tanzania (Brunker et al, ) and in close countries such as Turkey (Horton et al, ; Marston et al, ). From an epidemiological point of view, the identification of this transmission pattern underlines the importance of the wildlife reservoir in the maintenance and circulation of the virus.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Further, the analysis of metadata associated with these Iranian clades suggests frequent RABV transmissions between dog and wildlife animal populations, and vice versa. Such a complex transmission pattern has already been identified in other regions such as Tanzania (Brunker et al, ) and in close countries such as Turkey (Horton et al, ; Marston et al, ). From an epidemiological point of view, the identification of this transmission pattern underlines the importance of the wildlife reservoir in the maintenance and circulation of the virus.…”
Section: Discussionmentioning
confidence: 59%
“…Tanzania (Brunker et al, 2018) and in close countries such as Turkey (Horton et al, 2015;Marston et al, 2017). From an epidemiological point of view, the identification of this transmission pattern underlines the importance of the wildlife reservoir in the maintenance and circulation of the virus.…”
Section: Discussionmentioning
confidence: 92%
“…In general, a natural assumption is that the movement of pathogens and hosts and the intensity and amount of contacts between them always plays a role and should be incorporated into epidemiological analyses. For example, studies have shown the significant impact of the social network among giraffes coinciding with the patterns of direct transmission of E.coli among them [8], the global air-traffic volumes to be an important factor explaining the pandemic spread of influenza strains [9], and the road networks to explain the prevalence of measles cases in Niger [10] and the spread of rabies in Tanzanian dogs [11]. Spatial epidemiological analyses have utilized a diverse set of modeling tools, spanning from lattice, diffusion and metapopulation models to network models [12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods, models, and tools have been developed by ecologists to estimate population density or abundance by taking into account observation probability and its variation according to factors, such as time of day or season 132 rabies diffusion, and not their density. This implies that culling is ineffective for rabies control 67 .…”
Section: Test and Cullmentioning
confidence: 99%